The three-dimensional model of the political world: a philosophical interpretation - Shevchuk, Dmytro (Problemos, 2017)
The article is devoted to a philosophical analysis of the fundamental ontological principles of the political world. The author pays attention to the three main manifestations of the political: (i) antagonistic, which is presented through relations between friend and enemy; (ii) agonistic, which demonstrantes politics as a competition between different ideologies and positions; and (iii) imaginary and symbolic, which appears as strong connection between politics and socio-cultural situation. These manifestations of the political are often intertwined and realized as a network of relationships and political actions that create a three-dimensional model of the political world.